2009
DOI: 10.1007/s11199-009-9686-5
|View full text |Cite
|
Sign up to set email alerts
|

Women Are On, But Not In, the News: Gender Roles in Local Television News

Abstract: This investigation examined 580 news stories in the top three local television news programs in a Northeastern U.S. television market for a two-week period. Content analysis was used to determine whether or not there were gender differences in the prevalence of reporters and anchors and in the type of stories they reported. Analysis of newscasts revealed that female reporters were more likely to present human interest and health related stories, while males were more likely to present political stories. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 11 publications
5
40
0
Order By: Relevance
“…A possible explanation for the difference in valence might be that the roles that typically occur for men and women in the media differ. For example, it has been shown that media often represent women as ordinary people, whereas men are represented as experts and/or with power and high-status positions (Armstrong 2006, Desmond and Danilewicz 2010, Matud et al 2011. It is also plausible that expert or high-status positions are associated with more positively evaluated words.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the difference in valence might be that the roles that typically occur for men and women in the media differ. For example, it has been shown that media often represent women as ordinary people, whereas men are represented as experts and/or with power and high-status positions (Armstrong 2006, Desmond and Danilewicz 2010, Matud et al 2011. It is also plausible that expert or high-status positions are associated with more positively evaluated words.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in other national contexts has repeatedly found that men are more likely than women to be used as expert sources in newspapers (Armstrong and Nelson 2006;Zoch and VanSlyke Turk 1998) and on television, particularly for stories involving "hard news" topics such as politics (Cann and Mohr 2001;Desmond and Danilewicz 2010). When women do appear as sources on television news, it tends to be in connection with "softer" topics, such as health or lifestyle, and they often are represented in a "ritualized" way, offering a "contained and safe" representation of how actions taken in the public sphere affect those in the private sphere (Rakow and Kranich 1991, 16).…”
Section: Literature: News Sourcesmentioning
confidence: 99%
“…Hether and Murphy (2010) find women represent 38% of the major characters appearing in health storylines on popular primetime television programs. Male sources also appear almost three times more often than female sources in newspaper coverage of same-sex marriage (Schwartz 2010) and nearly twice as often in local television news coverage of a variety of topics (Desmond and Danilewicz 2010). In music videos drawn from five music-oriented television networks, male characters outnumber females by a ratio of 3 to 1 (Turner 2010).…”
Section: Under-representation Holds Across Multiple Media and Contentmentioning
confidence: 99%